Why methods matter: Approaching multimodality in translation research - Tuominen, Tiina; Jiménez Hurtado, Catalina; Ketola, Anne Maria (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2019)
The study of multimodal phenomena calls upon translation scholars to cross disciplinary boundaries and adopt a range of theoretical and methodological approaches. The diversity of the multimodal landscape brings about research challenges that must be carefully addressed to ensure that these research efforts yield useful and credible results. This special issue is dedicated to a discussion on how to engage in multimodal translation research: how traditional research methods can be adapted and what kinds of novel approaches can be adopted or developed in order to deal with a diversity of multimodal data. In this introduction, we first discuss definitions of mode and multimodality and reflect on the nature of multimodality as a topic of research within Translation Studies. We then explain our rationale for dedicating the special issue to research methods and introduce three areas of multimodal translation research that, in our view, merit particular attention from a methodological point of view. Finally, we introduce the articles contained in this special issue.